Fabrication of capillary force induced DNA template Ag nanopatterns for sensitive and selective enzyme-free glucose sensors - Shakir, Sehar; Saravanan, Jayachandran; Rizan, Nastaran; Jusice Babu, K.; Aziz, Md. Abdul; Phang, Siew Moi; Periasamy, Vengadesh; Gnana Kumar, George Peter (Elsevier, 2018)
The self-patterned silver (Ag) nanowires on Indium Tin Oxide (ITO) were developed and exploited as the enzyme-free sensor probes for glucose detection. Deoxyribonucleic acid (DNA) template increased the capillary force channels of Ag and facilitated the homogeneous and high mobility of Ag-DNA toward the scribe via the coffee ring effect. The subsequent removal of DNA template from Ag-DNA/ITO through the enzymatic hydrolysis process led to the formation of Ag nanowires on ITO. Under alkaline conditions, Ag nanopatterns developed on ITO realized the considerable enzyme-free glucose sensor performances. The fabricated sensor system is reproducible and stable and was pertained with an analysis of spiked human blood serum, where it provided excellent recoveries. Thus these findings have not only showered insights on the self assembly of Ag nanoparticles without the exploitation of any surfactants and harsh conditions but have also provided the fundamental perceptive on the influences of self-assembled nanowires in enzyme free glucose sensor applications.